B-Cell Deficiency Exacerbates Inflammation and Bone Loss in Ligature-Induced Experimental Periodontitis in Mice - Zeng W; Liu G; Luan Q; Yang C; Li S; Yu X; Su L (Dove Medical Press, 2021)
Wenmin Zeng,1 Guojing Liu,1 Qingxian Luan,1 Chunyu Yang,1 Shiyi Li,1 Xiaoqian Yu,1 Li Su2 1Department of Periodontology, Peking University School and Hospital of Stomatology, Beijing, People's Republic of China; 2Center of Medical and Health Analysis, Peking University, Beijing, People's Republic of ChinaCorrespondence: Xiaoqian YuDepartment of Periodontology, Peking University School and Hospital of Stomatology, Beijing, 100081, People's Republic of ChinaEmail Y_PK@163.comLi SuCenter of Medical and Health Analysis, Peking University, Beijing, 100191, People's Republic of ChinaEmail lisu76@bjmu.edu.cnObjective: Periodontitis, one of the most prevalent chronic oral infectious diseases in humans, is induced by the breakdown in the balance between the biofilm and host immune system. Previous studies have shown the presence of large numbers of B cells in periodontitis lesions, implicating that B lymphocytes play a predominant role during the pathogenesis of periodontitis. This study aimed to investigate the role of all B cells in the initiation of periodontitis.Methods: Experimental periodontitis was induced in B cell-deficient (CD19Cre) mice and wild-type (WT) control mice by 5-0 silk ligation around the maxillary second molar. Four weeks after ligation, alveolar bone loss was determined by micro-computed tomography. The levels of inflammatory cytokines and receptor activator of NF-κB ligand (RANKL)/osteoprotegerin in periodontal lesions were analyzed using real-time quantitative polymerase chain reaction, enzyme-linked immunosorbent assay, and immunohistochemistry. Lymphocyte populations in the cervical lymph nodes and spleen and among the peripheral blood mononuclear cells were detected by flow cytometry.Results: B-cell deficiency resulted in increased severity of alveolar bone loss in mouse experimental periodontitis, which was associated with increased osteoclast activity and upregulated RANKL expression in the periodontal lesions. In addition, gingiva cytokine expression profiles were shifted to T helper type 1 (Th1) and Th17 in the CD19Cre mice with ligature-induced periodontitis compared with WT mice. In addition, a reduced CD4+/CD8+ T cell ratio was observed in the CD19Cre mice.Conclusion: B-cell deficiency exacerbates the inflammation and alveolar bone loss in ligature-induced experimental periodontitis in mice, implicating that B cells may overall play a protective role in the initiation of periodontitis.Keywords: periodontitis, experimental periodontitis, alveolar bone loss, B lymphocytes